Measurement of solubility and metastable curves for crystallization processes - Huang, Yahui. (2009)
In this project, the use of turbidimetry in the measurement of the solubility and metastability has been established through the use of Paracetamol as the solute and water as the solvent. The method has been found to be generally effective in detecting the onset of dissolution, complete dissolution and onset of nucleation during the studies. Operational difficulties during the investigations, however, impede the reliability and validity of the results obtained. In the solubility investigation, the solubility of Paracetamol in water was measured via the polythermal method and the experimental results agree relatively well with that of literature, with less than 4.5% difference observed for each point. The metastability investigation, on the other hand, did not produce conclusive results. The lack of adequate control over the cooling rate was identified to a major cause since the factors to be investigated cannot be singled out to be the only affecting factor during the experiments. It is recommended that turbidimetry be incorporated in the isothermal method of solubility measurement to expand its application to other compounds which solubility are not as well-established and may not increase with temperature, and introduce better process control, especially with regard to temperature, to achieve more accurate metastability results.